Case report: A rare occurrence of a huge mediastinal mass from disseminated prostate carcinoma - Kai, Ming Teah; Chin, Pei Bong; D Kamarudin D Mudin; Soe May Zaw; Shankaran Thevarajah; Yeap, Boon Tat (Elsevier Ltd, 2021)
Background: Prostatic carcinoma is the commonest malignancy among men. It usually metastasizes to the spine and regional lymph nodes. However, it is extremely rare for it to metastasize to the mediastinum. Case presentation: An elderly man presented to us with progressive onset of bilateral lower limb weakness which was associated with thoracic radiculopathy and urinary incontinence. An urgent magnetic resonance imaging (MRI) of the spine showed severe cord compression with enlarged prostate and superior mediastinal mass. A computed tomography (CT) guided biopsy of the mediastinal mass was suggestive of prostatic malignancy. An emergency posterior instrumentation and fusion (PSIF) in prone position was successfully done. Histopathological examination of the spine showed malignant glandular tissues, suggestive of prostate. Discussion: A huge mediastinal mass can compromise the cardiorespiratory system and is very challenging for the anaesthetist to safely secure the airway for surgical procedures. Androgen deprivation therapy (ADT) for patients with metastatic prostatic carcinoma can be achieved either by medical castration or with bilateral orchidectomy. Conclusion: It is extremely uncommon for a prostatic carcinoma to metastasize to the mediastinum. Patients with a huge mediastinal mass possess risks of cardiorespiratory collapse perioperatively. Chemoradiotherapy and androgen deprivation therapy (ADT) can be utilized for metastatic prostatic carcinoma with good outcomes.